Do we need more patient‐friendly treatment options for overactive bladder (OAB)?. Issue 6 (21st June 2021) - Gerig, Nel; Cameron, Tracy; Arora, Samir; Spear, Jessica; Lescozec, Laura; Zhang, Mingming
Abstract: Aims: To collect feedback from subjects diagnosed with overactive bladder (OAB) on its impact on their quality of life, their satisfaction with current treatment options, and to assess nonsurgical, tibial nerve stimulation as a treatment option. Methods: Subjects were asked a variety of questions about the impact of OAB on their lives, their satisfaction with current and previous treatment approaches. Subjects evaluated the comfort of a nonworking prototype garment and were given electrical stimulation over their posterior tibial nerve to assess comfort and tolerability. Electromyographic (EMG) signals were recorded. Results: A total of 40 subjects with OAB symptoms were evaluated in the study. Urgency (55%), frequency (47.5%), nocturia (40%), and incontinence (30%) were the most bothersome symptoms. At the time of the study only 32.5% of the subjects were treating their OAB symptoms. Of those that had tried and discontinued treatments, most had failed medications ( n  = 14) due to no improvements or side effects. Only 2 subjects found stimulation to be uncomfortable before an EMG signal could be detected. The most common word used to describe the feeling of stimulation was "constant, " followed by "tingling, " "vibrating, " and "comfortable." Conclusions: Most subjects who had tried OAB treatments were dissatisfied and discontinued their use. A new patient‐friendly approach to OAB therapy that delivers efficacy but overcomes drawbacks associated with currently available treatments is needed. Subjects found electrical stimulation over the tibial nerve to be comfortable and tolerable and this should be considered as an alternative treatment approach for OAB.